Organisational Nationalisation - Seizing Control of an Organisation without Transfers of Property Rights on the Example of Housing Cooperatives in People's Poland - Piotr Eckhardt (Bratislava Law Review, 2024)
In all Central and Eastern European countries during the period of the establishment of state socialism after World War II, nationalisation involving the state taking over ownership of certain categories of property in order to build an economic system in line with the new ideological principles took place. In Poland, large land estates, enterprises belonging to basic branches of the economy, or all real estate in the city of Warsaw were nationalised. The nationalisation of housing cooperatives contradicted the official declarations of the People's Poland authorities, who promised to support cooperative movement. However, a number of legal regulations were introduced with the help of which the People's Poland authorities took control over housing cooperatives in order to, at first, practically force them out of operation and, later, instrumentally use them to implement the state's housing policy. Centralisation of cooperative movement and hierarchical subordination of cooperatives to state-controlled associations were carried out. The economic activities of the housing cooperatives were subordinated to the principles of a centrally planned economy. The possibility of creating new cooperatives was restricted, and the authorities reserved the right to liquidate existing ones. The order in which cooperatives allocated housing to their members was superimposed. Later, cooperatives were forcibly merged, and the area in which they could operate was restricted. Cooperative self-government was partly transformed into local state administration. In the case of housing cooperatives in People's Poland we cannot speak of proper nationalisation because there were no transfers of ownership. However, all other effects of nationalisation took place, but were achieved by other means. Such measures can be described as organisational nationalisation, which was also carried out in other spheres in People's Poland.